2021
DOI: 10.3390/su132011510
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Corporate Social Responsibility and the Executive Compensation on Implicit Cost of Equity: Evidence from French ESG Data

Abstract: This research aimed to evaluate the effect of corporate social responsibility (CSR) and executive incentive compensation based on the achievement of sustainability goals on the implicit cost of equity. To test the study’s hypotheses, the authors applied linear regressions on panel data using the Thomson Reuters ASSET4 and Thompson Institutional Brokers Earnings Services (I/B/E/S) database of a sample of 154 French ESG firms over the 2015–2020 period. Our results show that CSR activities lower the cost of equit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 54 publications
0
28
0
Order By: Relevance
“…First, we used the time of COVID-19 as an alternative indicator of the independent variable and ordinary least square estimation, and second, we added two variables to the original regression models. We identified book value per share (BVPS), which has been relied upon in previous studies (e.g., Chouaibi et al 2021 ; Broadstock et al 2021 ), and total liabilities (TOTLIAB) and added them to the regression model as control variables; then, we re-estimate the random effects model.…”
Section: Resultsmentioning
confidence: 99%
“…First, we used the time of COVID-19 as an alternative indicator of the independent variable and ordinary least square estimation, and second, we added two variables to the original regression models. We identified book value per share (BVPS), which has been relied upon in previous studies (e.g., Chouaibi et al 2021 ; Broadstock et al 2021 ), and total liabilities (TOTLIAB) and added them to the regression model as control variables; then, we re-estimate the random effects model.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 shows that after dividing by 100, the highest ESG score is 0.6411, the lowest ESG score is 0.0579, the average ESG score is 0.2149 and the standard deviation is 0.0733. This shows that there are listed companies' ESG performance differences [5].…”
Section: Measurement and Date Analysismentioning
confidence: 90%
“…Henriksson et al (2018) showed, that better ESG score allows companies to obtain cheaper loans, higher credit rankings and lower cost of equity capital. On a sample of 154 French ESG companies in the years 2015-2020, Chouaibi et al (2021) showed that corporate social responsibility (CSR) activities lower the cost of equity capital, thus they are important to shareholders' financing and investment decisions. According to the results of research conducted by Raimo et al (2020) the increase of ESG disclosure reduces the cost of equity capital.…”
Section: Literature Reviewmentioning
confidence: 99%